Regional Economic Outlook, April 2017, Asia and Pacific : Preparing for Choppy Seas - Salgado, Ranil (Regional Economic Outlook, 2017)
The Asia-Pacific region continues to be the world leader in growth, and recent data point to a pickup in momentum. We expect the region to expand by 5.5 percent in 2017, up from 5.3 percent in 2016. Accommodative policies will underpin domestic demand, offsetting tighter global financial conditions. However, the risks to the outlook, on balance, are slanted to the downside. A possible shift toward protectionism in major trading partners could suppress Asia's trade, while the continued tightening of global financial conditions and economic uncertainty could trigger capital flow volatility. A bumpier-than-expected transition in China would also have large negative spillovers to the region. Beyond the short term, many parts of Asia face secular headwinds from population aging and slow productivity growth. These challenges call for domestic policies that support growth while boosting resilience and inclusiveness. To sustain long-term growth, structural reforms are needed to deal with challenges from demographic transition and to boost productivity.